An Immune Suppression-associated EBV-positive Anaplastic Large Cell Lymphoma With a BRAF V600E Mutation. (January 2019) - Gru, Alejandro A.; Williams, Eli; Junkins-Hopkins, Jacqueline M.
Abstract : Iatrogenic lymphoproliferative disorders have been described in patients receiving immunosuppressive/immunomodulatory agents outside the transplantation setting. Novel biological agents such as TNF-α blockers and JAK-inhibitors have also proven to be effective in many disorders including rheumatoid arthritis, inflammatory bowel disease (ulcerative colitis and Crohn disease), psoriasis, and others. A significant dilemma exists in those lymphoproliferative disorders associated with immunosuppressants and rheumatologic conditions, that relies on whether the association of the process is with the medication or the underlying autoimmune condition. In the current case report, we describe an extraordinary case of Epstein-Barr virus–positive anaplastic large cell lymphoma, in association with rheumatoid arthritis and the use of JAK-inhibitors. Comprehensive molecular testing (fluorescence in situ hybridization, OncoScan microarray, pyrosequencing) was done comparing sequential biopsies in this patient from skin and lung, which revealed a driving mutation in the BRAF V600E gene, a crucial finding, given the potential use of targeted therapy in this pathway.